Therapeutically relevant features of botulinum toxin drugs. (February 2020) - Dressler, Dirk
Abstract: Botulinum toxin (BT) drugs were introduced in the late 1980s. They are now used worldwide in a large number of indications. This huge market and its future opportunities have attracted a number of companies about to enter the competition with projects to develop new BT drugs. We want to outline features of BT drugs that are relevant for their therapeutic use and - with that - are also relevant to compare and to evaluate new BT drugs and to guide their further development. BT drugs may vary in their content of botulinum neurotoxin, complexing proteins and excipients. Their manufacturing is complex and directly influences core features of the final drug. It includes breeding, purification, botulinum neurotoxin activation, stabilisation, potency control, labelling and testing, specific biological activity and packaging. The manufacturer's support concerning product documentation and support, reliability of drug supply, counterfeit protection and - last but not least - competitive pricing is also important. Further developments include the indication spectrum, the market penetration, the drug's duration of action, liquid preparations, transdermal applications, improving antigenicity and a bio-similarity registration process. Most projects, however, will try to produce Botox® analogs at reduced sale prices. Highlights: Many new botulinum toxin drugs are currently under development. We outline botulinum toxin drug features that are relevant for their therapeutic use, for their comparison and for their further development. Development goals include the indication spectrum, the market penetration, the drug's duration of action, liquid preparations, transdermal applications, improving antigenicity and a bio-similarity registration process. Most projects, however, will try to produce Botox® analogs at reduced sale prices.